2017
DOI: 10.1039/c6tc04989c
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular non-covalent interactions as a strategy towards controlled photoluminescence in copper(i) complexes

Abstract: Easily accessible N-donor ligands enable tunable photoluminescence via steric modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 57 publications
(63 reference statements)
2
30
0
Order By: Relevance
“…Thep reparation of the new mechanophore and its selective incorporation in PUs was the first objective of our study.W eb ased our mechanophore design on an ew class of recently developed phosphorescent complexes that were shown to reversibly respond to mechanical stress (CuN 4 , Figure 1b). [8,9] Themechanism governing their force-induced response,depicted in Figure 1b,isconceptually different from those found in common organic mechanophores. [9] Instead of bond scission and related irreversible transformations,t hese copper halide complexes vary their photoluminescence (PL) via aforce-induced restriction of their intramolecular isomerization that represents an on-radiative relaxation process.…”
mentioning
confidence: 87%
“…Thep reparation of the new mechanophore and its selective incorporation in PUs was the first objective of our study.W eb ased our mechanophore design on an ew class of recently developed phosphorescent complexes that were shown to reversibly respond to mechanical stress (CuN 4 , Figure 1b). [8,9] Themechanism governing their force-induced response,depicted in Figure 1b,isconceptually different from those found in common organic mechanophores. [9] Instead of bond scission and related irreversible transformations,t hese copper halide complexes vary their photoluminescence (PL) via aforce-induced restriction of their intramolecular isomerization that represents an on-radiative relaxation process.…”
mentioning
confidence: 87%
“…The starting point of our investigation was marked by the recent development of a family of Cu(I) phosphorescent complexes that have showed a remarkable sensitivity of the PL properties to the local environment . Namely, the subtle variations of the substituent bulk in the macrocyclic cyclophane‐inspired ligand resulted in dramatic changes of the quantum yield in the solid state.…”
Section: Properties and Composition Of Polymer Samples Prepared For Tmentioning
confidence: 99%
“…(a) Reproduced with permission. [ 174 ] Copyright 2017, The Royal Society of Chemistry; (b–d) Reproduced with permission under the terms of the Creative Commons CC BY license. [ 176 ] Copyright 2018, the Authors.…”
Section: Mechanical Stimulation Of Directional Supramolecular Interacmentioning
confidence: 99%
“…[173] Analogous to these investigations with NHC complexes, Khusnutdinova and co-workers developed a series of photoluminescent iodo-copper pyridinophane (CuN 4 -I) complexes (Figure 12a). [174] The emission color of the CuN 4 -I complexes could be tuned by varying either the counterion or the bulkiness of the pendant groups attached to the pyridinophane, since these parameters influence the unique excited state geometries. The CuN 4 -I complex was covalently incorporated into the hard segments of a PU and the authors observed an increase in the photoluminescence (PL) intensity of the complex when the material was subjected to tensile deformation.…”
Section: Organometallic Complexes As Mechanoresponsive Moietiesmentioning
confidence: 99%